2019
DOI: 10.35940/ijitee.i1024.0789s219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of E-Service Quality on Repurchase Intention: Testing the Role of E-Satisfaction as Mediator Variable

Abstract: Recent developments in information and communication technology have contributed to tremendous economic efficiency. Companies that can take advantage of the sophistication of information and communication technology can operate more efficiently. Firm efficiency will tend to lower product prices and faster delivery time. It is expected to increase consumer satisfaction and repurchase intention. This study investigates the influence of e-service quality on repurchase intention with satisfaction as mediating vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
3
0
3
Order By: Relevance
“…Kepercayaan pelanggan sendiri berasal dari pihak-pihak yang sebelumnya belum saling mengenal baik dalam hal interaksi maupun bertransaksi (Bachmann 2015). Kepercayaan pelanggan merupakan keyakinan dalam menggantungkan dirinya terhadap pihak lain dalam hal bertransaksi (Lestari and Ellyawati 2019). Penelitian Putera, Dalle, and Syafari (2021); Abdullah, Apriliyanto, and Junianingrum (2023) mengemukakan bahwa terdapat pengaruh kualitas pelayanan terhadap kepercayaan pelanggan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kepercayaan pelanggan sendiri berasal dari pihak-pihak yang sebelumnya belum saling mengenal baik dalam hal interaksi maupun bertransaksi (Bachmann 2015). Kepercayaan pelanggan merupakan keyakinan dalam menggantungkan dirinya terhadap pihak lain dalam hal bertransaksi (Lestari and Ellyawati 2019). Penelitian Putera, Dalle, and Syafari (2021); Abdullah, Apriliyanto, and Junianingrum (2023) mengemukakan bahwa terdapat pengaruh kualitas pelayanan terhadap kepercayaan pelanggan.…”
Section: Pendahuluanunclassified
“…Kepercayaan pelanggan berasal dari pihak-pihak yang sebelumnya belum saling mengenal baik dalam hal interaksi maupun dalam hal bertransaksi (Bachmann 2015). Adapun Kepercayaan pelanggan merupakan keyakinan dalam menggantungkan dirinya terhadap pihak lain dalam hal pertukaran (Lestari and Ellyawati 2019). Kepercayaan pelanggan merupakan evaluasi terhadap jual beli yang dipilih berdasarkan alternatif yang sekurang-kurangnya sama atau bahkan mencapai nilai lebih dari harapan konsumen (Radionova-Girsa and Lahiža 2017).…”
Section: Kepercayaan Pelangganunclassified
“…thus this study supports research (Lolika, 2021) which states that ease of use has a positive and significant effect on repurchase intention. (Lestari, 2019) also states that ease of use has a positive and significant effect on repurchase intention. Research (Monica, 2022) states that ease of use has a positive and significant effect on repurchase intention.…”
Section: Path Coefficient P-value Upsilon Explanationmentioning
confidence: 99%
“…Mensah and Mensah (2018) and Phuong and Dai Trang (2018) reported the positive effect of service quality and satisfaction on repurchase intention. Leonnard (2018) and Lestari and Ellyawati (2019) noted the mediating role of satisfaction between service quality and repurchase intention and concluded that improved service quality tends to cause customer satisfaction that leads to repurchase intentions. More recently, Wilson et al (2019) surveyed the e-commerce industry of five continents (Asia, Australia, North and South America, and Europe) to investigate the effects of service quality and website design quality on satisfaction and repurchase intention.…”
Section: E-service Quality In the Retail Industry (3) Service Quality...mentioning
confidence: 99%